The Role of Youth and Technology in Modern Islam - Hanifah, Cahyarani Triayu; Sudjatnika, Tenny (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This paper explores the dynamic role of Muslim youth in embracing and utilizing technology within the context of modern Islam. As digital natives, young Muslims actively engage with online platforms to disseminate Islamic values, establish spiritual communities, and modernize religious education. Through a qualitative-descriptive approach, this research highlights the integration of Islamic teachings with contemporary technology, while analyzing the digital hijrah movement as a case study. The findings show that technology, when paired with proper religious literacy, becomes an effective tool for dakwah, education, and activism. However, challenges such as radicalism, disinformation, and superficial religiosity must be addressed. This paper concludes that youth are not only beneficiaries of religious transformation but also its primary agents.